Stronger brain activation for own baby but similar activation toward babies of own and different ethnicities in parents living in a multicultural environment - Raghunath, Bindiya Lakshmi (2023)
Specific facial features in infants automatically elicit attention, affection, and nurturing behaviour of adults, known as the baby schema effect. There is also an innate tendency to categorize people into in-group and out-group members based on salient features such as ethnicity. Societies are becoming increasingly multi-cultural and multi-ethnic, and there are limited investigations into the underlying neural mechanism of the baby schema effect in a multi-ethnic context. Functional magnetic resonance imaging (fMRI) was used to examine parents' (N = 27) neural responses to (a) non-own ethnic in-group and out-group infants, (b) non-own in-group and own infants, and (c) non-own out-group and own infants. Parents showed similar brain activations, regardless of ethnicity and kinship, in regions associated with attention, reward processing, empathy, memory, goal-directed action planning, and social cognition. The same regions were activated to a higher degree when viewing the parents' own infant. These findings contribute further understanding to the dynamics of baby schema effect in an increasingly interconnected social world.